Options for Long Distance Passenger Land Transport Infrastructure Expansion. Analysis Regarding Network-based Sustainable Development. (2016) - Dinu, Oana; Burciu, Stefan
Abstract: In the global reality of intense competition for financial resources, models for transport infrastructure and operational technologies development are to be taken into consideration in order to ensure that both service and physical network provision serves society's wider need. Proposed paper presents a detailed methodology for the substantiated choices of transport infrastructure development in case of long distance haul and high speed passenger travel, adequate for efficient resources consume (space, energy, finances). Practical aspects are revealed in the present comparative study regarding space and equivalent energy consumption, conducted for two land infrastructures, highway and high speed rail, connecting the same origin and destination points. As a result, although both services have their benefits and costs, high speed rail is recommended as a sustainable development action, ranking better than highway infrastructure. Recommendations concerning methodological clarifications and practical aspects are made in order to insure the best practice considering a sustainable network based transport infrastructure assessment process.